The quality of teaching and professional development of teachers : a Portuguese study - Herdeiro, Rosalinda (2013)
This paper is part of a research study undertaken with Portuguese teachers. The main objective is to understand the impact of recent educational legislation on the quality of teaching and the professional development of teachers. In this context the following research questions were formulated: ‘ Do the education policies of the government encourage teacher development? ’ , ‘ Will opportunities for teacher development be created in schools? ’ , ‘ Will the goal of improving the quality of teaching be achieved in education contexts sustained by teaching mal- aise ? ’ This paper seeks to explain the perceptions of elementary school teachers recounted in written and oral biographical narratives and in three discussion groups set up for the purpose. The professional experiences recounted by the teachers suggest outcomes different from those foreseen by educational policy-makers, thus emphasising the weaknesses and inapplicability of the core objectives established by recent Portuguese legislation.